Associations between maternal obesity and severe maternal morbidity: Findings from the French EPIMOMS population‐based study. Issue 1 (17th October 2018) - Siddiqui, Ayesha; Azria, Elie; Howell, Elizabeth A.; Deneux‐Tharaux, Catherine; ,
Abstract: Background: Maternal obesity is increasing. There is growing evidence of its effect on severe maternal morbidity. We assessed prepregnancy obesity as an independent risk factor for severe maternal morbidity by timing and cause. Methods: We designed a case‐control analysis within the EPIMOMS prospective population‐based study conducted in six French regions in 2012‐2013 (182 309 women who delivered at ≥22 weeks). Cases were all women who experienced severe maternal morbidity during pregnancy to 42 days postpartum as per a multicriteria definition derived by national expert consensus (n = 2540, severe maternal morbidity prevalence 1.4%). Controls were randomly selected from the same health centres (n = 3651). The association between obesity and severe maternal morbidity was assessed from fitting multivariable logistic regression models: overall, by timing (antepartum and intrapartum/ postpartum), and by cause. Results: Prepregnancy obesity was associated with overall severe maternal morbidity (adjusted odds ratio [OR] 1.34, 95% confidence interval [CI] 1.14, 1.59) and antepartum severe maternal morbidity (OR 2.07, 95% CI 1.61, 2.65), but not with intra/postpartum severe maternal morbidity (OR 1.15, 95% CI 0.96, 1.38). Among antepartum severe maternal morbidity, severe hypertensive disorders were most strongly associated with obesity (OR 2.50, 95% CI 1.85, 3.40) but the risk of antepartum severe maternal morbidity due to other causes was also increased among obese women (OR 1.64, 95% CI 1.13, 2.37). Obesity was not associated with severe postpartum haemorrhage (OR 1.12, 95% CI 0.92, 1.37). Conclusion: Obesity is associated with an increased risk of antepartum, but not intra/ postpartum, severe maternal morbidity.